The Decreased Treg Cells Number Associated with Retinal Lesion Size in Ocular Toxoplasmosis - Ovi Sofia; Muna Amalia; Herryanto Thomassawa; Loeki Enggar Fitri; Seskoati Prayitnaningsih; Hani Susianti (Interdisciplinary Perspectives on Infectious Diseases)
Introduction. The imbalance of the immune response is an important factor contributing to the incidence of ocular toxoplasmosis (OT). Regulatory T cells (Treg) play a key role in maintaining the balance between Th1 and Th17 immune responses, while interleukin-27 (IL-27) levels are related to the differentiation of Th17 cells. This study analyzes the differences in the number of Treg cells and the level of IL-27 between OT patients and seropositive individuals without ocular lesions and its correlation with retinal lesion size. Methods. This analytic observational study, conducted for 8 months, involved 11 OT patients and 10 seropositive individuals without ocular lesions. All subjects underwent a comprehensive ophthalmological examination. Retinal lesions were documented by fundus photographs and the size was measured using Digimizer 4.2.2.0 software. Isolation of peripheral blood mononuclear cells (PBMC) was performed to measure the number of Treg cells using flow cytometry and interleukin-27 levels were assessed using the Sandwich enzyme-linked immunosorbent assay (ELISA) technique. Data were analyzed with SPSS. Result. The number of Treg cells in the OT group (47.16 ± 15.66%) was lower than in the seropositive group without the ocular lesions (62.86 ± 17.08%) (p=0.029). The serum IL-27 levels in the OT group were not significantly different from the seropositive group without the ocular lesions (p=0.360). The number of Treg cells was significantly related to retinal lesion size (p=0.043), with a correlation coefficient of −0.648, indicating a strong and inverse correlation. There was no significant correlation between serum IL-27 levels and retinal lesion size (p=0.556). Conclusion. Ocular toxoplasmosis patients have a low number of Treg cells that are inversely related to the retinal lesion size. The size of the retinal lesion increases as the number of Treg cells decreases.